PERLINDUNGAN HAK ASASI MANUSIA PEKERJA KONTRAK (OUTSOURCING) DI KOTA AMBON - Barzah Latupono (SASI, 2016)
as a creature of God Almighty who also have rights. One form is a contract worker rights are guaranteed to be protected in accordance with the values of religion and humanity as well as of Pancasila and the destination country listed in the 1945 Constitution Protection of workers intended to guarantee the basic rights of workers and ensure equality of opportunity and treatment without discrimination on anything for the welfare of workers and their families with regard to the progress of the business and the interests of employers. Legislation related to the protection of workers namely Law No. 13 of 2003 on employment and the implementing regulations of the law in the field of employment.